358 Phase 3 trial of tumor treating fields concomitant with weekly paclitaxel for platinum-resistant ovarian cancer: ENGOT-ov50/GOG-329/INNOVATE-3. (13th November 2020) - Vergote, I; Salutari, V; Cibula, D; Korach, J; Samartzis, EP; Sehouli, J; Fossati, R; Martin, AG; Tsibulak, I; Slomovitz, B; Coleman, R; Monk, B; et al.
Abstract : Background: Tumor Treating Fields (TTFields) are a non-invasive, antimitotic cancer therapy. The Phase 2 INNOVATE study demonstrated safety of TTFields/weekly paclitaxel in 31 PROC (platinum-resistant ovarian cancer) patients (Vergote Gyn Onc 2018); efficacy: median PFS 8.9 months, 25% partial response, 71% clinical benefit and 61% 1-year survival rate. This phase 3 ENGOT-ov50/GOG-329/INNOVATE-3 study [NCT03940196 ] investigates TTFields plus weekly paclitaxel in PROC patients. Study Design: Patients (N=540) will have PROC (RECIST V1.1) within 6 months of last platinum therapy with maximum of 2–5 prior lines of systemic therapy, ECOG 0–1 and no peripheral neuropathy >grade1. Patients with primary refractory disease will be excluded. Patients will be randomized 1:1 to weekly paclitaxel alone or weekly paclitaxel (starting of dose 80 mg/m2 weekly for 8 weeks, and then on Days 1, 8, and 15 for subsequent 28-day cycle ) plus TTFields (200 kHz for 18 hours/day and continued if no progression in the abdominal or pelvic regions ('in-field region') per RECIST V1.1. Clinical follow-up will be performed q4w, with radiological follow-up (CT or MRI scans of the abdomen and chest) q8w. The primary endpoint is overall survival. Secondary endpoints: PFS, objective response rate, AEs, and quality of life (EORTC QLQ-C30 with QLQ-OV28). Sample size (n=540) will detect an increase in median OS from 12 to 16 months (HR 0.75). Data Monitoring Committee (DMC) meeting (March 2020) concluded that data to-date showed no safety issues and recommended trial continuation.